Currencies and cultures the impact of culture on economic policies and the foundations of money - Noël, Noel Mark (Cambridge Scholars Publishing, 2019)
Why cultures are different can be examined through the multifaceted lens of their currencies, their economic policies, and the very foundations of how money works. Anyone who has traveled abroad immediately senses the cultural differences, even before learning about the language, politics, or history of the people. The tourist is promptly faced with strangely priced goods and services, an unknown currency of dubious value, and an alien system of payment, trade, and exchange. An investigation into the origins and evolution of money explains much about the behavior of people and their culture.00The collection of coins and money often begins with an inquiry into the history of a currency and other payment media used to resolve debts and exchange goods. Coin collecting can lead to a compelling interest in the study of cultural differences as numismatists have come to appreciate the semantic connection between numisma (coinage) and nomos (customs) with nonos (laws). Those interested in economics and business would find, through the study of numismatics, a wealth of information?the equivalent of a life-long education?not only in the study of coins and currencies, but also about people and their history
Keywords: Geschichte; Kultur; Wirtschaftspolitik; Numismatik; Währung; Coins; Money